Efektivitas Aromaterapi Lavender Pada Pasien Dislokasi Lutut Dengan Nyeri Akut Di RST Wijayakusuma Purwokerto - Sumboko, Priyo; Ridho S, Muhammad; Sekar Siwi, Adiratna; Indira, Indira (NHM PRESS, 2025)
Knee dislocation is a condition where the bones in the knee shift from their normal position. It can occur in the thigh bone (femur), shin bone (tibia) and kneecap bone (patella). Pain is an unpleasant symptom experienced by patients with knee dislocation. Pain in knee dislocation can be treated with various alternatives, both pharmacologically and non-pharmacologically. Pharmacologically, it can be treated with analgesic drugs. One natural method that is considered effective in reducing pain is lavender aromatherapy. This case study aims to describe the application of Lavender Aromatherapy in Knee Joint Dislocation Patients with Acute Pain in the Village of RST Wijayakusuma Purwokerto. Case studies were carried out by observation for 2x meetings and interventions providing lavender aromatherapy for 2 days on February 24-25, 2025. The results of the case study of the application of lavender aromatherapy on the first day the patient was still in pain by showing a decrease in the pain scale on the second day. On the first day, the patient's level before being given lavender aromatherapy therapy with a pain scale of 6 (moderate pain) after being given lavender aromatherapy therapy became 5 (moderate), on the second day there was a significant decrease in pain scale after being given lavender aromatherapy therapy, namely scale 2 (mild pain). Lavender aromatherapy in Knee Joint Dislocation Patients with Acute Pain in RST Wijayakusuma Purwokerto Village is effective in reducing pain applied for 2x24 hours showing significant results from a pain scale of 6 (moderate pain) to a pain scale of 2 (mild pain).